Predictive modelling in paleoenvironmental reconstruction: The micromammals of Manot Cave, Israel. Issue 160 (November 2021) - Comay, Orr; Weissbrod, Lior; Dayan, Tamar
Abstract: This paper describes the micromammalian remains and paleoenvironment of the Upper Paleolithic sequence of Manot Cave (46-34 ka), southern Levant. Micromammal remains were identified from Ahmarian (46-42 ka), Levantine Aurignacian (38-34 ka) and post-Levantine Aurignacian (34-33 ka) layers. To identify taphonomic agents, molar digestion was modelled for seven local raptor species, and model predictions were compared with observed digestion scores in the Manot Cave material. Raptor species differed significantly in molar digestion patterns, allowing us to identify Tyto alba as the bone accumulator in the Ahmarian and Post-Levantine Aurignacian units. Data were insufficient for species-level identification of the taphonomic agent in the Levantine Aurignacian. Günther's voles ( Microtus guentheri ) were dominant, though woodland species ( Apodemus spp., Sciurus anomalus and Dryomys nitedula ) also occurred through the entire sequence. Manot Cave furnished the first fossil record of the Eurasian snow vole ( Chionomys nivalis ) in the southern Levant during the Late Pleistocene and its first secure record of the water vole ( Arvicola terrestris ) outside the Hula Valley. Records of other taxa ( Acomys dimidiatus and D. nitedula ) provide the earliest occurrence datum in the region. Using counts of both identified specimens and distinct elements (lower first molars) we modelled paleoenvironmental conditions through both Weighted Averaging Partial Least Squares regression and a qualitative analysis considering niche preferences of species. Model predictions indicate the unexpectedly pronounced dominance of open habitats compared to present conditions near the cave, though the occurrence and abundance of woodland species also indicate some woodland expansion relative to the preceding Middle Paleolithic period. Combining statistical models and species niche considerations we show that the time span between the Ahmarian, Levantine Aurignacian and post-Levantine Aurignacian was marked by a clear-cut climatic oscillation to cooler and likely wetter conditions.